Predialysis vascular access creation: To whom and when - Escoli,Rachele (2017)
Aims: The optimal timing of predialysis vascular access surgery remains uncertain. This study goal was to evaluate the influence of kidney function and clinical characteristics at predialysis vascular access surgery on the likelihood of initiating hemodialysis during follow-up. Methods: Our study retrospectively identified all patients undergoing predialysis arteriovenous fistula creation between 2012-2015. We assessed 3 outcomes: frequency of hemodialysis initiation, death before hemodialysis initiation, and dialysis-free survival after vascular access creation. Multiple variable logistic regression analyzed which factors predicted initiation of dialysis. Results: The study involved 202 patients. Using multiple variable logistic regression, 5 factors were associated with hemodialysis initiation: estimated glomerular filtration rate <10 mL/min/1,73m2 at vascular access placement [OR 4.7, CI: 1.98-8,60, p=0.005], diabetes [OR 2.14, CI: 1.07-4,30, p=0.033], proteinuria>1gr/24 hours [OR 1.88, CI: 0.95-3.71, p=0.049], higher phosphorus levels [OR 6.25, CI: 1.39-13.05, p=0.017] and glomerular filtration rate drop ³3mL/min/1.73m2 in the year preceding vascular surgery [OR 1.67, CI: 0.81-3.45, p=0.016]. Cancer and congestive heart failure were associated with dead before starting dialysis [OR 5.9, CI: 1.15-9.78, p=0.038 and OR 2.4, CI: 1.3-3.9, p=0.021, respectively] and higher hemoglobin (>10g/dL) without erythropoietin stimulating agent levels with survival without needing dialysis [OR 2.34, CI: 1.09-4,58, p=0.028]. Conclusions: Optimizing the timing of vascular access creation in predialysis patients requires consideration not only of the kidney function but also comorbidities such as diabetes, estimated glomerular filtration rate decline in the preceding year and degree of proteinuria